2012
DOI: 10.1093/beheco/ars140
|View full text |Cite
|
Sign up to set email alerts
|

Alternative behavioral measures of postconflict affiliation

Abstract: Post-conflict (PC) affiliation refers to positive social interactions that occur after fights. Although this behavior has been widely studied, its functions are rarely tested. We examine a potential function of PC third-party affiliation (affiliation between former opponents and bystanders) in rooks and jackdaws by investigating the hypothesis that conflicts lead to further aggression and that PC third-party affiliation increases to reduce such aggression. The results show that PC affiliation reduces PC aggres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
48
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(54 citation statements)
references
References 67 publications
3
48
3
Order By: Relevance
“…In ravens, Fraser & Bugnyar () found that post‐conflict affiliation offered to the victim was more likely to occur if the bystander shared a valuable relationship with the victim and after intense conflict. Subsequent studies (Logan, Emery & Clayton, 2013 a ; Logan, Ostojić & Clayton, 2013 b ) using a slightly different methodology, showed that jackdaws ( Corvus monedula ) and Eurasian jays ( Garrulus glandarius ) engage in third‐party affiliation initiated by both combatants and bystanders. Colonial jackdaws showed third‐party affiliation with mates; despotic and territorial jays with any individual, not just mates.…”
Section: Sympathetic Concernmentioning
confidence: 99%
“…In ravens, Fraser & Bugnyar () found that post‐conflict affiliation offered to the victim was more likely to occur if the bystander shared a valuable relationship with the victim and after intense conflict. Subsequent studies (Logan, Emery & Clayton, 2013 a ; Logan, Ostojić & Clayton, 2013 b ) using a slightly different methodology, showed that jackdaws ( Corvus monedula ) and Eurasian jays ( Garrulus glandarius ) engage in third‐party affiliation initiated by both combatants and bystanders. Colonial jackdaws showed third‐party affiliation with mates; despotic and territorial jays with any individual, not just mates.…”
Section: Sympathetic Concernmentioning
confidence: 99%
“…So far, post‐conflict behaviours have been studied in four different corvid species: Eurasian jays (hereafter called jays; Garrulus glandarius ), jackdaws ( Corvus monedula ), ravens ( Corvus corax ) and rooks ( Corvus frugilegus ). While the use of third‐party affiliation has been shown in all four corvid species (Fraser & Bugnyar, ; Logan, Emery et al., ; Logan, Ostojić et al., ; Seed et al., ; Sima, Pika, & Bugnyar, ), only ravens seem also to show reconciliatory behaviour (Fraser & Bugnyar, ). One possible explanation is that the four corvid species differ in their use of post‐conflict behaviours.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the lack of reconciliation in some species may simply be the result of the existing social relationship structure (Seed et al., ). Except for the one study on ravens (Fraser & Bugnyar, ), all studied individuals lived in relatively similar social groups, characterised by (i) predominantly bonded pairs, and (ii) relatively low levels of agonistic interactions between pair partners (Logan, Emery et al., ; Logan, Ostojić et al., ; Seed et al., ). In these groups, third‐party affiliation (conflict with a non‐pair group member and post‐conflict affiliation with the pair partner)—rather than reconciliation—may thus represent the most beneficial post‐conflict behaviour to strengthen and advertise the prevailing pair bonds (Das, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations